LINGUISTIC ANALYSIS OF POLITICAL SPEECH - Narimanova Diyora Jalilovna (Bright Mind Publishing, 2025)
Political discourse holds a central position in modern linguistic studies, serving as a crucial component of discursive practice. It often conveys a strong sense of populism through various linguistic tools and strategies. The effectiveness of political discourse is largely determined by its objectives and intended outcomes. Language that resonates with the public’s sentiments and expressions has the power to engage audiences effectively. This article examines theoretical perspectives on political discourse and provides a linguistic analysis of its structure. Additionally, Barack Obama’s speech is analyzed from a linguistic standpoint.
Keywords: Political speech, political discourse, rhetoric, linguistic analysis, repetition, figurative language.